Training Needs for Transcending Nursing Professor-TutorConception at the Cuban University of Medical Sciences - Mendoza Jacomino, Alexander (2010)
In the twenty-first Century the concern to increase the quality of educational systems has grown considerably, urging us to professionalize teacher capabilities and to work continued education all along their professional careers. This, in turn, is based on the self-management of learning and also on activities directed to the professional development of true models of pedagogical practice. Departing from the assumption that calls for a change in the way professional development is understood, which emphasizes the need to move towards a model that would deal with the issue on an agreed-upon way-rather than a directive one, as it has traditionally happened- a new vision as to the way that professional development should be conducted is herein presented, namely that of Psycho-pedagogical Counseling, which goes from the mere transmission of knowledge onto the development of competencies according to the needs that have been identified by those taking part in the process.